2016
DOI: 10.1242/jeb.140566
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of the diapause transcriptome in apple maggot flies: winter regulation and post-winter transcriptional repression

Abstract: The duration of dormancy regulates seasonal timing in many organisms and may be modulated by day length and temperature. Though photoperiodic modulation has been well studied, temperature modulation of dormancy has received less attention. Here, we leverage genetic variation in diapause in the apple maggot fly, Rhagoletis pomonella, to test whether gene expression during winter or following spring warming regulates diapause duration. We used RNAseq to compare transcript abundance during and after simulated win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 76 publications
5
23
0
Order By: Relevance
“…Inspection of proteins significantly more abundant in the heads of diapause-destined females revealed several previously associated with increased stress hardiness including a putative small heat shock protein, a putative peptidoglycan recognition protein that could be involved in increased pathogen resistance, as well as glutathione S-transferase and thioredoxin, two proteins that have been implicated in ameliorating both oxidative stress and xenobiotic stress. Similar processes of increased hardiness to pathogens, oxidative stress and heat shock protein expression have commonly been found in other “omics” studies of insect diapause (Ragland et al, 2010; Poelchau et al, 2013; King and MacRae, 2015; Poupardin et al, 2015; Qi et al, 2015; Meyers et al, 2016 as some examples). Two proteins that stand out as being associated with development of synaptic activity in nervous systems, bruchpilot and syntaxin (Broadie et al, 1995; Wagh et al, 2006; Short, 2013), were also more abundant in diapause-destined females and have previously been associated with diapause in other insects and C. elegans worms (Ailion and Thomas, 2003; Ragland et al, 2011).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Inspection of proteins significantly more abundant in the heads of diapause-destined females revealed several previously associated with increased stress hardiness including a putative small heat shock protein, a putative peptidoglycan recognition protein that could be involved in increased pathogen resistance, as well as glutathione S-transferase and thioredoxin, two proteins that have been implicated in ameliorating both oxidative stress and xenobiotic stress. Similar processes of increased hardiness to pathogens, oxidative stress and heat shock protein expression have commonly been found in other “omics” studies of insect diapause (Ragland et al, 2010; Poelchau et al, 2013; King and MacRae, 2015; Poupardin et al, 2015; Qi et al, 2015; Meyers et al, 2016 as some examples). Two proteins that stand out as being associated with development of synaptic activity in nervous systems, bruchpilot and syntaxin (Broadie et al, 1995; Wagh et al, 2006; Short, 2013), were also more abundant in diapause-destined females and have previously been associated with diapause in other insects and C. elegans worms (Ailion and Thomas, 2003; Ragland et al, 2011).…”
Section: Resultssupporting
confidence: 66%
“…Increased stress hardiness is commonly a facet of diapause in many insect species and transcripts or proteins associated with stress hardiness have been identified in many studies (MacRae, 2010; Ragland et al, 2010; Poelchau et al, 2013; Poupardin et al, 2015; Qi et al, 2015; Meyers et al, 2016). Heat shock proteins in particular are associated with stress hardiness and are often highly expressed in diapausing individuals (Rinehart et al, 2007; Aruda et al, 2011; Pérez-Hedo et al, 2012; Lu et al, 2013; King and MacRae, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the pioneering paper of Denlinger and coworkers (29), a number of studies have described differences in gene transcription linked to insect diapause (20,(30)(31)(32)(33)(34)(35)(36). Indeed, some authors have attempted to integrate these studies and to detect commonalities in the diapause transcriptional profiles of different species, searching for the hypothetical genetic toolkit of diapause (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies are needed to identify the specific genes affecting eclosion time in R. pomonella, test for signatures of selection, and discern their demographic histories. In this regard, Ragland, Egan, Feder, Berlocher, and Hahn (2011) and Meyers et al (2016) showed marked differences between host races in gene expression patterns prior to diapause termination and suggested genes in the Wnt and TOR signaling pathways as candidate loci. Whole-genome DNA sequencing is also needed examine the apple race for soft vs. hard selective sweeps around candidate loci (Hermisson & Pennings, 2005), the former predicted under the standing variation hypothesis, while the latter is expected if new mutations enabled the shift to apple.…”
Section: Standing Variation and Rapid Adaptive Evolutionmentioning
confidence: 99%